Actuator Saturation Compensation for Fast Tool Servo Systems With Time Delays - Liu, Pengbo; Song, Yuanyuan; Yan, Peng; Sun, Yujing (IEEE access, 2021)
Fast tool servo systems with high precision and high speed pose significant challenges to servo control at the nano-scale. The saturation of the control actions, time delays and system uncertainties further complicate the control challenges. To address these problems, we propose a Smith predictor based robust anti-windup scheme in this article, such that high performance servo with nano-accuracy can be achieved in the case of saturations, time delays and model uncertainties. According to the input/output based equivalent representation, the saturation nonlinearity is transformed to the dead zone nonlinearity fulfilling a sector condition. Based on the Popov criterion, the stability conditions for the anti-windup compensator are derived, which are further formulated as an H_∞ optimization problem with robustness against model uncertainties. The effectiveness of the proposed control architecture is verified through real-time experiments, where excellent servo performance, saturation compensation and robustness are demonstrated, outperforming existing results.